Cell migration: a novel aspect of pancreatic stellate cell biology. Issue 5 (1st May 2003) - Phillips, P A; Wu, M J; Kumar, R K; Doherty, E; McCarroll, J A; Park, S; Pirola, R C; Wilson, J S; Apte, M V
Abstract : Background: Pancreatic stellate cells (PSCs), implicated as key mediators of pancreatic fibrogenesis, are found in increased numbers in areas of pancreatic injury. This increase in PSC number may be due to increased local proliferation and/or migration of these cells from adjacent areas. The ability of PSCs to proliferate has been well established but their potential for migration has not been examined. Aims: Therefore, the aims of this study were to determine whether cultured rat PSCs have the capacity to migrate and, if so, to characterise this migratory capacity with respect to the influence of basement membrane components and the effect of platelet derived growth factor (PDGF, a known stimulant for migration of other cell types). Methods: Migration of freshly isolated (quiescent) and culture activated (passaged) rat PSCs was assessed across uncoated or Matrigel (a basement membrane-like substance) coated porous membranes (pore size 8 μm) in the presence or absence of PDGF (10 and 20 ng/ml) in the culture medium. A checkerboard assay was performed to assess whether the effect of PDGF on PSC migration was chemotactic or chemokinetic. Results: Cell migration was observed with both freshly isolated and passaged PSCs. However, compared with passaged (culture activated) cells, migration of freshly isolated cells was delayed, occurring only at or after 48 hours of incubation when the cells displayed an activated phenotype. PSC migration through Matrigel coated membranes was delayed but not prevented by basement membrane components. PSC migration was increased by PDGF and this effect was predominantly chemotactic (that is, in the direction of a positive concentration gradient). Conclusions: (i) PSCs have the capacity to migrate. (ii) Activation of PSCs appears to be a prerequisite for migration. (iii) PDGF stimulates PSC migration and this effect is predominantly chemotactic. Implication: Chemotactic factors released during pancreatic injury may stimulate the migration of PSCs through surrounding basement membrane towards affected areas of the gland.